Perfil cognitivo, fragilidade, sintomas depressivos e sobrecarga de idosos cuidadores em comunidades rurais - Brigola, Allan Gustavo (2016)
This study aimed to analyze the relationship between cognition, frailty, urden and depressive symptoms in older caregivers from rural communities of Sao Carlos, Brazil. The study was exploratory and analytical. Approved by the Ethics Committee of the interviews were conducted in homes with two or more elderly. We used scales for basic activities (BADL) and instrumental (IADL) of daily living evaluation(Katz and Lawton), sociodemographic and care information forms, the Addenbrooke’s Cognitive Examination - Revised (ACE-R), that includes the Mini Mental State Examination (MMSE) for global cognitive assessment and domains (Attention/Orientation, Memory, Verbal Fluency, Language and Visospatial Skills), frailty evaluation according to Fried’s phenotype (weight loss, fatigue, weakness, slowness and low levels of physical activity), Zarit Burden interviw for assessment of caregiver burden and, in addition, the Geriatric Depression Scale (GDS). We interviewed in homes 85 pairs of elderly (85 elderly care recipients and their older caregivers 85). The elderly who were receiving care, most were male (n = 60; 70.5%), mean age of 72 years and 3.78 years of education, pre-frail (42.8%) and with significant frequency cognitive impairment (CI) (45.9%). The elderly caregivers were mostly women (76.7%). The average age was 69 years and 4.35 years of education. Regarding the context of care, 89.4% were taking care of their spouses, an average of 145.68 months (about 12 years), and received help for care (76.5%). The average score for ACE-R was 68.78 points and 24.44 points for the MMSE. 15.3% of caregivers showed evidence for CI, 9.4% were classified as frail, 52.9% were pre-frails and 37.6% non-frails/robusts, 67.1% were classified with a small burden, 24.7% had a moderate burden, 8.2% had severe burden and 84.7% showed no depressive symptoms. Comparison analysis showed that groups with higher levels of burden and frailty had worse cognitive performance and more depressive symptoms compared to those non frails and less burdened. Regression analysis showed that being pre frail represents a decrease of almost 12 points in the ACE-R, in the univariate model, and 8.6 points in the multiple model, interestingly being frail decreased 28 points in the cognitive battery if it is analyzed in the univariate model. In both models, theburden is associated with poor cognitive performance, This association is more intense in the univariate model (β = -7.83; p = 0.02). Being a burdened caregivers decreased nearly 8 points in cognitive battery (p = 0.04), as evidenced in the multiple model. This shows that not only the frail condition, but also burden condition represent a negative relationship with the cognitive performance in older caregivers in rural context. The older caregiver in this context certainly experiences working within the available resources. Longitudinal studies may be ways for in-depth knowledge on the subject. It is recommended the study of variable stress and its relationship to cognitive frailty in caregivers and seek to understand the differences between rural and urban.